Alteration of Stress Distribution Patterns in Symptomatic Valgus Instability of the Elbow in Baseball Players: A Computed Tomography Osteoabsorptiometry Study. (April 2016) - Funakoshi, Tadanao; Furushima, Kozo; Momma, Daisuke; Endo, Kaori; Abe, Yuichiro; Itoh, Yoshiyasu; Fujisaki, Kazuhiro; Tadano, Shigeru; Iwasaki, Norimasa
Background: Repetitive valgus stress applied during a throwing motion can lead to various elbow disturbances, including ulnar collateral ligament (UCL) injury. Subchondral bone density reportedly reflects the cumulative force on a joint surface under actual loading conditions. Purpose: (1) To evaluate the distribution of subchondral bone density across the elbow joint in asymptomatic baseball pitchers and symptomatic valgus instability pitchers and (2) to clarify the alterations in stress distribution pattern associated with symptomatic UCL insufficiency pitching activities. Study Design: Controlled laboratory study. Methods: Computed tomography (CT) imaging data were collected from the dominant-side elbow of 7 nonathletic volunteers (controls), 12 asymptomatic pitchers (asymptomatic group), and 12 symptomatic valgus instability pitchers with UCL insufficiency (symptomatic group). Bone mineral density across the elbow joint was measured with CT osteoabsorptiometry. A 2-dimensional mapping model was divided into 4 areas of the distal end of the humerus and 5 areas of the ulna with the radial head. The locations and percentages of high-density areas on the articular surface were quantitatively analyzed. Results: High-density areas in the asymptomatic and symptomatic groups were found in the anterolateral and posteromedial parts of the humerus and in the radial head, posteromedial to the ulna. The high-density areas in the anterior and posteromedial of the humerus, the radial head, and the posteromedial part of the ulna in the controls were smaller than those in the baseball group. In the symptomatic group, the percentages of high-density areas in the anterolateral part of the humerus (mean, 36.3%; 95% CI, 31.9%-40.7%) and the anterolateral part of the ulna (mean, 31.7%; 95% CI, 24.3%-39.1) were significantly greater than those in the asymptomatic group ( P = .047 and P < .0001, respectively). Conclusion: Symptomatic UCL insufficiency was associated with characteristic high-stress distribution patterns on the anterolateral part of the capitellum and the anterolateral part of the ulna. The current results indicate that symptomatic UCL insufficiency produces excessive and cumulative stress in the elbow joint. Clinical Relevance: The information obtained from the CT images can useful for early detection of overstress conditions of the elbow joint.